Free flap head and neck reconstruction in the elderly: what is the impact on quality of life? - FERRI, A. (Acta Otorhinolaryngol Ital, 2019)
Morphofunctional reconstruction is a pivotal aspect in the surgery of head and neck neoplasms: nowadays, microvascular free flap surgery represents the gold standard. In choosing the surgical technique, the effects on residual quality of life, especially in elderly people, usually considered more fragile and so often excluded from microsurgical procedures, must be taken into account. This multicentre study evaluated the quality of life index in patients more than 75 years of age and who underwent to head and neck microsurgical reconstruction. Data from patients aged > 75 years at the time of major head and neck reconstruction conducted with free flaps between 1 January 2005 and 30 June 2015 were analysed retrospectively. We administered the Italian version of Quality of Life questionnaire SF-36, at least 24 months after surgery. Results were compared to those for the general Italian population of the same age. We enrolled 39 patients with an average age of 80.6 years. The results did not differ significantly from the reference population. The international literature has already shown that chronologic age is not a valid parameter to determine the surgical treatment modality. Even considering the quality of residual life, our study supports the indication for free-flap reconstruction of head and neck defects in the elderly, confirming its effectiveness in this population.